Development of Flipbook-based Local History Teaching Modules for High Schools Students - Fathurrahman, Fathurrahman; Yuliantri, Rhoma Dwi Aria; Susanto, Heri; Rochgiyanti, Rochgiyanti; Pebriantika, Leni; Akmal, Helmi (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the feasibility of a flipbook-based local history teaching module. This research used the research and development (R&D) method with the ADDIE model. This research was conducted at SMA Negeri 7 Banjarmasin and SMA Negeri 10 Banjarmasin. Field trials were carried out in class XI, totaling 30 students each. Data were obtained through observation, interviews, and questionnaires. Meanwhile, data analysis used descriptive quantitative and qualitative. The local history teaching module developed was declared very feasible to use. This assessment is based on the average score of the material and media experts. Material experts 1 and 2 gave scores of 4.69 and 4.76, while media experts 1 and 2 gave scores of 4.74 and 4.66. The overall score is in the very feasible category, indicating the good quality of the module to be used in learning. This local history teaching module is expected to help teachers in delivering local history material more interestingly and effectively, and can increase students' interest and understanding of local history.